2002
DOI: 10.1177/0075424202026002930
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Effect of Natural Convection on Heat Transfer in Mineral Wool

Abstract: In Denmark and a number of other countries convection in fibrous materials is considered non-existent when calculating heat transmission as well as when designing building structures. The current investigation serves to examine whether considering natural convection non-existent in fibrous materials is a fair assumption to use in present and future building structures. In order to facilitate the experimental work, an apparatus with a metering area of 3 × 1 m2 was designed for measuring the effect of convectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The measured permeability of the insulation material perpendicular and parallel to the main fibre direction was 1.62·10 -9 m² and 4.25·10 -9 m² respectively for glass wool specimens from the same batch as used in the test section. This is in line with previous results from Økland (1998) and Dyrbøl et al (2002). Uvsløkk et al (2010) measured a permeability of 2.5·10 -9 m² and 5.1·10 -9 m² perpendicular and parallel to the main fibre direction respectively.…”
Section: Permeability Of Insulation Materialssupporting
confidence: 93%
See 1 more Smart Citation
“…The measured permeability of the insulation material perpendicular and parallel to the main fibre direction was 1.62·10 -9 m² and 4.25·10 -9 m² respectively for glass wool specimens from the same batch as used in the test section. This is in line with previous results from Økland (1998) and Dyrbøl et al (2002). Uvsløkk et al (2010) measured a permeability of 2.5·10 -9 m² and 5.1·10 -9 m² perpendicular and parallel to the main fibre direction respectively.…”
Section: Permeability Of Insulation Materialssupporting
confidence: 93%
“…However, the calculations only included horizontally oriented insulation and the permeability was rather high (.7.5 3 10 29 m 2 ). Dyrbøl et al (2002) performed measurements of convection in three different types of insulations. The test section was tested in both the vertical and horizontal positions.…”
Section: Wallsmentioning
confidence: 99%
“…The effect of natural convection on heat transfer in mineral wool was studied in Ref. 6, and the radiative behavior of mineral wool was studied in Refs. 7 and 8.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning natural convection in roofs, Shankar et al [17], Dyrbøl et al [18] and Wahlgren et al [19] have reported valuable calculations, respectively measurements and a thorough literature review concerning horizontal roofs. However, limited literature is available concerning pitched roofs.…”
Section: Convection and The Effect On Thermal Performance In Walls Anmentioning
confidence: 99%